Unicystic Ameloblastoma Presenting as a Multilocular Radiolucency in the Anterior Mandible: A Case Report - Nigel R. Figueiredo; Manoj Meena; Ajit D. Dinkar; Sonam Malik; Manisha Khorate (Tabriz University of Medical Sciences, 2015)
Ameloblastomas are tumors of odontogenic epithelial origin. The term unicystic ameloblastoma is used to describe cystic lesions with clinico-radiographic features resembling an odontogenic cyst, but histologically showing the presence of ame-loblastomatous epithelium lining part of the cyst cavity. A large majority of lesions are found in the mandible, and usually cause a painless swelling of the jaws. They can be radiographically subdivided into 'dentigerous' and 'non-dentigerous' types. The unicystic ameloblastoma is believed to be less aggressive than a solid/multicystic ameloblastoma, and thus has a more favorable response to enucleation and curettage. This case report presents a case of unicystic ameloblastoma with a multilocular radiographic appearance in the anterior mandible of a 45-year-old female patient, along with a literature review of the topic.